2013
DOI: 10.1063/1.4826261
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the binding free energies of charged species based on explicit-solvent simulations employing lattice-sum methods: An accurate correction scheme for electrostatic finite-size effects

Abstract: The calculation of a protein-ligand binding free energy based on molecular dynamics (MD) simulations generally relies on a thermodynamic cycle in which the ligand is alchemically inserted into the system, both in the solvated protein and free in solution. The corresponding ligand-insertion free energies are typically calculated in nanoscale computational boxes simulated under periodic boundary conditions and considering electrostatic interactions defined by a periodic lattice-sum. This is distinct from the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
386
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(389 citation statements)
references
References 153 publications
(350 reference statements)
3
386
0
Order By: Relevance
“…4547 The finite-size error has several physical origins, including the periodicity induced net charge interaction and undersolvation, discrete solvent effects, as well as residual integratd potential effects. 47 Rocklin et al recently showed that, for a system neutralized with counter-ions, the finite-size error in the charging free energy of a ligand (with +1 or −1 charge) is dominated by the discrete solvent effects due to an offset potential that compensates for the potential generated by discrete solvent. 47 The corresponding offset energy in charging a titratable group is given as 47 …”
Section: Methods and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…4547 The finite-size error has several physical origins, including the periodicity induced net charge interaction and undersolvation, discrete solvent effects, as well as residual integratd potential effects. 47 Rocklin et al recently showed that, for a system neutralized with counter-ions, the finite-size error in the charging free energy of a ligand (with +1 or −1 charge) is dominated by the discrete solvent effects due to an offset potential that compensates for the potential generated by discrete solvent. 47 The corresponding offset energy in charging a titratable group is given as 47 …”
Section: Methods and Implementationmentioning
confidence: 99%
“…47 Rocklin et al recently showed that, for a system neutralized with counter-ions, the finite-size error in the charging free energy of a ligand (with +1 or −1 charge) is dominated by the discrete solvent effects due to an offset potential that compensates for the potential generated by discrete solvent. 47 The corresponding offset energy in charging a titratable group is given as 47 …”
Section: Methods and Implementationmentioning
confidence: 99%
“…Furthermore, some readers may question the appropriateness of using the Ewald background plasma correction for charged systems. 1,118120 Previous works have suggested that one should perform many, short simulations to obtain an average Δ G from independent estimates rather than from running a few, long simulations. 121124 The error estimation described in the Computational Details section accounts for correlation within a simulation, but it does not attempt to estimate the error incurred from finite sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Δ G finite–size represents the correction to the electrostatic energy calculated with particle mesh Ewald under periodic boundary conditions for charged systems. 22 No error bars are given for ΔGresnormalL and Δ G finite–size , as they were calculated analytically. The error bar of Δ G (pH 4.6) was estimated by combining the errors in Δ G (pH ref ) and the pH-dependent corrections.…”
Section: Figurementioning
confidence: 99%